Church and Ministry - Egmond, A. van,; Keulen, Dirk van, (Studies in Reformed Theology;, 1999)
The International Reformed Theological Institute (IRTI) was founded in 1995. Its purpose is to create a platform where Reformed theologians from all over the world can meet each other, become acquainted with each other's work, discuss theological issues and stimulate each other in scholarly theological research. The members of IRTI present their work in the series Studies in Reformed Theology . Thus, the volumes of this series offer a perspective on the theological insights and spirituality of Reformed theologians all over the world. The third volume of Studies in Reformed Theology contains the contributions to the second international conference of the IRTI. Leading theme of the conference was 'Church and Ministery'. Thoughts and experiences, problems and solutions were shared concerning the position of the church and the training of ministers in Reformed churches. Most of the devotional contributions to the conference have been included in this volume as well.